"Daughter Cyst" Sign: A Sonographic Finding of Ovarian Cyst in Neonates, Infants, and Young Children - Lee, Hee-Jung; Woo, Seung-Ku; Kim, Jung-Sik; Suh, Su-Jhi (American journal of roentgenology (1976), 2000)
The purpose of this study was to assess the value of the "daughter cyst" sign, a sonographic finding of neonatal ovarian cysts, in differentiating ovarian cysts from other cystic masses in neonates, infants, and young children. In a prospective study, 23 neonates, infants, and young children (age range, 1 day to 36 months) with a lower abdominal cystic mass underwent sonography. We defined the daughter cyst sign as the presence of a small cyst along the wall of a cystic mass. The diagnosis of ovarian cyst was made when this sign was present. Detailed pathologic correlation was available in four ovarian cysts. The size, wall thickness, and contents of the cysts were also evaluated. The 23 cystic lesions included ovarian cyst (n = 11), lymphangioma (n = 3), enteric duplication cyst (n = 3), enteric cyst (n = 1), meconium pseudocyst (n = 2), hydrometrocolpos (n = 2), and urachal cyst (n = 1). The daughter cyst sign was seen in nine (82%) of 11 ovarian cysts but in none of the other cystic lesions. Sensitivity, specificity, and positive predictive value of the daughter cyst sign for differentiating ovarian cysts from other cystic lesions were 82%, 100%, and 100%, respectively. The daughter cyst corresponded to an ovarian follicle on pathologic examination. The daughter cyst sign is a specific sonographic finding for an ovarian cyst and may be useful in differentiating uncomplicated ovarian cysts from other cystic masses in neonates, infants, and young children.